Transendocardial injection of expanded autologous CD34+ cells after myocardial infarction: Design of the EXCELLENT trial - Jerome Roncalli; François Roubille; Nicolas Meyer; Giulio Pompilio; Lionel Leroux; Philippe Henon; Guillaume Trebuchet; Anthony Criquet; Matthieu deKalbermatten; Eric Saloux; Alain Manrique; Pierre‐Yves Marie; et al. (ESC Heart Failure)
Abstract Aims The extent of irreversible cardiomyocyte necrosis after acute myocardial infarction (AMI) is a major determinant of residual left ventricular (LV) function and clinical outcome. Cell therapy based on CD34+ cells has emerged as an option to help repair the myocardium and to improve outcomes. The dose of CD34+ cells and the route of administration are two important factors that will determine the clinical effectiveness of the approach, provided it is robust and feasible. Here, we describe the rationale and design of the multicentre open‐label randomized controlled phase I/IIb trial evaluating the safety and the likelihood of efficacy of transendocardial expanded CD34+ cell administration in patients presenting with AMI and a reduced LV ejection fraction. Methods Patients with a large AMI and LV ejection fraction <50% are randomized 3:1 to transendocardial expanded CD34+ cell injection plus standard of care or standard of care alone. Patients randomized to intervention are treated with lenograstim for 5 days before 220 ± 10 mL blood cell harvest from which autologous CD34+ cells are purified and expanded for 9 days using an automated good manufacturing practice compliant platform. The primary endpoint is the incidence of major adverse cardiac events over 6 months. The main secondary endpoints are LV end systolic volume index and the viability of the infarcted segments. Conclusions Autologous CD34+ cell therapy is currently limited by technological constraints. This is the first trial to evaluate the feasibility and potential effect of CD34+ cells after automated expansion and transendocardial administration in patients with large AMI.